DEMOGRAPHIC POLICIES IN THE CONTEXT OF GLOBALIZATION. AN ANALYSIS OF THE RIGHT TO MARRIAGE IN ISLAM - GHENCEA, Flavia Lucia; Nicolau, Ingrid Ileana; Topor, Roxana Elena; Comșa, Ana Maria (Annals of Spiru Haret University. Economic Series, 2020)
In the context of globalization, the demographic geometry is suffering major changes that have significant effects on the social economy of states. For any society, change is an element with great development potential but also with an extremely dangerous major component: the fear felt at individual level. The last few years have witnessed a populist xenophobic trend (at least in Europe), if we refer to the crisis of immigrants, mostly Muslims, who are knocking at Europe’s borders. Starting from the certainty that fear has its source in ignorance, the present paper has two objectives: on the one hand, to bring more insight into some particular aspects related to the Islamic family and to the rights of women within this social institution and, on the other hand, to make a presentation of some demographic policies of the European family.